2021
DOI: 10.1016/j.copsyc.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

How cultural learning and cognitive biases shape religious beliefs

Abstract: What explains the ubiquity and diversity of religions around the world? Widespread cognitive tendencies, including mentalizing and intuitive thinking, offer part of the explanation for recurrent features of religion, and individual differences in religious commitments. However, vast diversity in religious beliefs points to the importance of the cultural context in which religious beliefs are transmitted. Cultural evolutionary theory provides the basis of a unified explanation for how cognition and culture inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…The approach of the cognitive science of religion might furthermore be particularly helpful: It has a long tradition of assessing what types of religious beliefs persist (Norenzayan et al, 2006), and how and where people come to endorse such beliefs (Atran & Henrich, 2010). Moreover, its close collaboration with evolutionary scientists has provided enduring insights on how such beliefs came to be in the first place, through evolved cognitive architecture and cultural learning (Gervais et al, 2011;White et al, 2020). Extensions of the dual pathway model to broader (cultural) evolution research are suggested to be similarly worthwhile (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The approach of the cognitive science of religion might furthermore be particularly helpful: It has a long tradition of assessing what types of religious beliefs persist (Norenzayan et al, 2006), and how and where people come to endorse such beliefs (Atran & Henrich, 2010). Moreover, its close collaboration with evolutionary scientists has provided enduring insights on how such beliefs came to be in the first place, through evolved cognitive architecture and cultural learning (Gervais et al, 2011;White et al, 2020). Extensions of the dual pathway model to broader (cultural) evolution research are suggested to be similarly worthwhile (cf.…”
Section: Discussionmentioning
confidence: 99%
“…We are working with a common definition of cognitive bias as judgmental or perceptual errors; that is, "cases in which human cognition reliably produces representation that are systematically distorted compared to some aspect of objective reality" (Haselton, Nettle, & Murray, 2016, 968; see also Kahneman & Tversky, 1996). Finally, we realize Mentalizing Mistakes 3 that the highly contested term "religiosity" can be used to refer to a wide range of phenomena and that social context is important for explaining the occurrence of specific forms of religious commitments across cultures (White, Baimel & Norenzayan, 2021). For the purposes of this article, however, we are interested in religious belief understood as explicit assertions or implicit assumptions about the existence of gods.…”
Section: Distinguishing Mentalizing Ability From Bias In God Beliefsmentioning
confidence: 98%
“…These biases include mind‐body dualism, teleological reasoning (the tendency to attribute purpose to natural phenomena), anthropomorphism, and a hypersensitive representational system for social agents. Indeed, some research suggests that these biases are associated with belief in the supernatural (see Atran & Norenzayan, 2004; White et al, 2021, for reviews). For example, perceptions of the mind and body as entities with distinct functions (i.e., mind‐body dualism), coupled with teleological reasoning, predicted belief in God among Canadian undergraduates and U.S. adults (Willard & Norenzayan, 2013).…”
Section: Belief In Supernatural Unobservables As Real: the Central Ro...mentioning
confidence: 99%